Management Model for Chengdu to be the Sports Capital of the People’s Republic of China - An, Bo; Hongsaenyatham, Prakit (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: From the perspective of the sports industry, with the continuous expansion of the sports consumption market, Chengdu's sports industry has shown a trend of diversified development, covering multiple fields such as sports event operation, sports training, sports equipment manufacturing and sales, and sports tourism. Although Chengdu has significant advantages in building a sports capital, there are still some problems. Therefore, this research aims to develop a management model for Chengdu to be the sports capital of the People’s Republic of China. Materials and Methods: This research employed a mixed methods approach. Through literature review and experts’ interviews with 11 experts, the questionnaire for Delphi was developed (IOC=0.90). The researcher invited 19 experts to conduct three rounds of Delphi consensus, aiming to create a management model for Chengdu to be the sports capital. Finally, 7 experts confirmed the developed management model using the connoisseurship method. The average and standard deviation are utilized to analyze the data obtained from the questionnaire; the consensus data is analyzed by using the median and interquartile range, with criteria set at a median of ≥ 3.50 and an interquartile range of ≤ 1.50.s Results: The management model for Chengdu to be the sports capital of the People’s Republic of China was developed based on POLC theory, which consists of planning 13 components, such as increasing the sports participation rate, enriching mass sports activities, improving the supply of sports facilities, and expand the scale of the sports industry. Organization 18 components, such as playing the role of a bridge, contacting and uniting all kinds of sports social organizations and sports workers in the city, organizing and carrying out sports competition exchanges, responsible for the promotion of the project and talent training, and provide fitness venues, equipment, and professional fitness guidance services to meet the needs of citizens. Leading 11 components, such as strengthening cooperation with schools, international exchanges, and cooperation to promote international cooperation, and sports facilities and infrastructure construction. Controlling 15 components, such as establishing an expert advisory committee, extensive soliciting of public opinions, formulating the performance evaluation index system, and strengthening supervision and inspection. Conclusion: The management model for transforming Chengdu into the sports capital of China is a comprehensive framework based on the PLOC theory, refined through expert input via the Delphi method. It emphasizes strategic planning to integrate sports into urban development, aiming to boost citizen participation, improve public health, and enhance the city's global competitiveness. Strong leadership focuses on developing infrastructure, fostering local and international sports events, and promoting youth sports, supported by coordinated efforts among government departments and sports organizations.